Development of technology of portland cement using gas condensate sludge recycling waste - Рыщенко, Татьяна Дмитриевна; Вяткин, Константин Игоревич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with the topical issue of increasing the energy efficiency of manufacturing construction materials, such as Portland cement, applying organic-mineral additives. Using gas industry waste - gas sludge as the organic-mineral additive is proposed. Gas sludge due to its chemical composition accelerates the rate of chemical reactions during firing the raw mix of Portland cement clinker, thereby saving energy. Energy saving is associated with a decrease in temperature of the relevant physicochemical reactions during the Portland cement clinker firing. The paper contains the analysis of theoretical and practical aspects of the problem, proposes solutions to improve the energy efficiency of Portland cement clinker production by applying the organic-mineral additive, in particular gas sludge, which lowers the temperature of chemical reactions, and also considers the features of chemical reactions in the process of Portland cement clinker firing using the gas sludge waste in the raw mix.